Peningkatan Keterampilan Menulis Cerita Pendek Melalui Media Lalipop Siswa Kelas VII-D SMP Negeri I Gedangan Sidoarjo - Suparmi, Meliana (Jurnal Lentera merupakan Jurnal Prodi Pendidikan Bahasa Indonesia yang berkala mempublikasikan artikel ilmiah dari hasil penelitian berupa pengajaran dan pendidikan Bahasa Indonesia. Secara khusus, jurnal ini berisi penelitian tentang pengajaran, pen, 2019)
ABSTRACT                 The writing ability of VII-D students in SMPN 1 Gedangan are still low. It is proved by their writing scores on the previous meeting about short story. Based on the previous meeting, 80% of the students scored under the minimum criteria of mastery learning, which means only 20% of them succeeded in writing short story. The data obtained from 32 students shows that only seven of them scored more than 65, while 25 of them scored under 65. Regarding on those condition, the researcher believes that there are two factors that influenced it; teacher and student. Thus, the researcher will use lalipop as one of the media to improve students? ability in writing short story.  There are three research problems that will be analyzed in this study. Those are (1) how is the improvement of students? ability in writing short story by using lalipop, (2) how is the change of students? behavior after joining class about writing short story using lalipop. Thus, the objectives of this study are (1) to describe the improvement of students? ability in writing short story by using song as a media (2) to describe the change of students? behavior after joining class about writing short story using lalipop. Moreover, this research is a classroom action research. There were two cycles, which are stage one and two. The subject of this study is student?s skill in writing short story using lalipop. There are two variables in this study, which are the ability to write short story and lalipop as a media. The data are collected through test, observation, journal, questionnaire, interview, and photo as documentation. This study used quantitative and qualitative as data analysis techniques. Those two techniques will be analyzed by comparing the result of the tests from the first cycle with the second cycle. Based on the data analyzed in this study, it can be concluded that by using lalipop as a media, the students? writing ability are improved. After using lalipop, there is also a significant change in the students? attitude toward writing class. The students of VII-D in SMPN 1 Gedangan became more enthusiast in learning process, especially in writing. Furthermore, by considering the results of the study above, it is hoped that Bahasa Indonesia teacher will use lalipop as a media in writing short story. Kata kunci: keterampilan,  menulis cerpen, media lalipop